Renal artery angiography in pediatric trauma using a national data set. Issue 5 (October 2020) - Edwards, Angelena; Passoni, Niccolo M.; Chen, Catherine J.; Schlomer, Bruce J.; Jacobs, Micah
Summary: Introduction: With limited pediatric renal trauma management literature, treatment pathways for children have been extrapolated from the adult population. A shift to non-operative management has led to higher renal preservation rates; however, characterization of endovascular intervention in the pediatric trauma population is lacking. Objective: This study uses the National Trauma Data Bank (NTDB), to evaluate renal outcomes after use of renal artery angiography. We hypothesized that patients undergoing renal artery angiography for renal trauma are unlikely to require additional surgical interventions. Study design: All children ≤18 years old treated for traumatic renal injuries from 2012 to 2015 were identified by the Abbreviated Injury Scaled Score (AISS) codes in the NTDB. AISS codes were converted to American Association for Surgery of Trauma (AAST) grades. ICD-9 codes were used to identify patients that had renal artery angiography, and additional renal interventions such as nephrectomy, partial nephrectomy, percutaneous nephrostomy tube or ureteral stent placement. Results: 536, 379 pediatric trauma cases were in the NTDB from 2012 to 2015, with 4506 renal injury cases identified. A total of 88 patients had renal artery angiography (ICD-9 88.45). Only 10% (n = 9) of patients who received renal artery angiography underwent an additional urological intervention. Of those nine, two patients were excluded due to renal angiography taking place after nephrectomy was performed. The remaining seven patients had high grade laceration (AAST grade 4-5). Overall, two patients underwent post angiography nephrectomies, two patients had partial nephrectomies, one percutaneous nephrostomy tube was placed (prior to partial nephrectomy), one aspiration of a kidney (prior to ureteral stent placement), and three had ureteral stent placements. Discussion: The limitations of this study include: the NTDB is a national dataset that is not population based, inclusion is limited to the first hospitalization, inaccuracies exist in encounter coding, and the database is lacking laterality of the renal injury. Based on nonspecific nature of ICD-9 coding for angioembolization, we are unable to discern the number of cases that subsequently had angioembolization after or at the time of angiography. Conclusion: Renal artery angiography in children remains a rare procedure, 88/4, 506, in children with renal trauma. In pediatric trauma cases that undergo renal artery angiography additional procedures are more common with higher grade injuries. Further studies are needed to create pediatric specific trauma management algorithms. Summary Table Patient Characteristics (N = 88/4506) Female 25 (29%) Age in years (median, IQR) 16 (13–18) Mechanism of trauma  Blunt trauma 88% (n = 77)  Penetrating trauma 9% (n = 8)  Unspecified 3% (n = 3) AAST Renal Injury Grade  Grade I 6  Grade II 10  Grade III 24  Grade IV 38  Grade V 10 Number patients who had urologic procedures performed after RAA 8% (n = 7) IQR = interquartile range; AAST = American Association for the Surgery of Trauma; RAA = Renal Artery Angiography.